ANALISIS KONSUMSI PANGAN BERBASIS PROTEIN HEWANI DI KABUPATEN LEBONG: PENDEKATAN MODEL AIDS (ALMOST IDEAL DEMAND SYSTEM) - Suryanty, Melly; Reswita, Reswita (Jurnal AGRISEP, 2016)
This paper analyze the food consumtion base-on animal protein in Lebong. The study estimated a demand model for food base-on animal protein by using Almost Ideal Demand System (AIDS) model. It also estimated demand elasticities for different food items by the models.  The result show that the demand model for food-based on animal protein can be explained by AIDS models. The model is consistent with demand theory. The coefficient of determination show range from 12.59 percent to 29.36 percent. However, the homogenity test for restriction parameters have not been explained by the model.  The estimated own-price elasticity of demand for Chicken, Goldfish and Egg indicated that if the price fell by 10% then the demand for the items would increase by 2.72%, 6.82%, and 9.05%, respectively. It show that the items are inelastic and necessities goods.  The income elasticity of demand for Chicken, Goldfish and Egg were 1.000, 0.999, and 1.000, respectively. It shows that all commodities are normal goods.  The estimates of cross price elasticity indicate that substitution effects of price change were not quite strong.